Antimicrobial susceptibility pattern of aerobes in diabetic foot ulcers in a South-Indian tertiary care hospital. (December 2018) - Sekhar M., Sonal; M.K., Unnikrishnan; Rodrigues, Gabriel Sunil; Vyas, Navya; Mukhopadhyay, Chiranjay
Highlights: Antimicrobial resistance is a major issue confronting healthcare providers and their patients. Empirical antimicrobial therapy should be composed of antimicrobials to cover Gram-positive and Gram-negative organisms. The antibiogram suggests that certain pathogens still remain sensitive to number of antimicrobial agents. No single antimicrobial agent can cover all possible pathogens isolated from diabetic foot infections. Abstract: Purpose: Diabetic foot infections (DFIs) are major public health concerns. In the view of the ever increasing burden of multidrug-resistant (MDR) organisms, improving the use of antimicrobial agents (AMAs) is a national priority. Objective of the study was to determine antimicrobial susceptibility (AMS) pattern of aerobes in DFIs. Methods: A cross-sectional study was conducted for a period of 3 years at Department of Surgery, Kasturba hospital, Manipal, India during which, 260 diabetic foot ulcer (DFU) patients admitted in the general surgery wards were enrolled for the study. These patients' culture specimens were observed as Gram-stained smears and cultured aerobically on blood agar and MacConkey agar plates. AMS test was performed by disc diffusion technique according to Clinical and Laboratory Standards Institute (CLSI) guidelines. Results: A total of 354 microbes were isolated from the ulcer wounds of 213 diabetic foot patients, with an average of 1.7 organisms per lesion. Monomicrobial infections were less common (n = 81; 31.2%) than polymicrobial infections (n = 132; 50.7%). Gram-negative bacteria were the most common among the isolates (n = 192; 54.2%). Aerobic Gram-positive Cocci accounted for 162 (45.8%) of all isolates. On the other hand, Staphylococcus aureus was the most frequently isolated aerobe (n = 106; 29.9%) followed by Pseudomonas aeruginosa (n = 91; 25.7%). Conclusion: AMS data from our study recommends that doxycycline would be the appropriate choice as single drug for empirical coverage for Gram-positive organisms. The most appropriate antibiotic for Gram-negative organisms is meropenem. One of the critical observations is the presence of Acinetobacter, an MDR isolated from DFIs, which is either relatively or totally resistant to all the AMAs tested.